Self-efficacy and quality of life among patients undergoing continuous ambulatory peritoneal dialysis - Enikmawati, Anik; Hastuti, Weni; Purwaningsih, Heni; Enawati, Sri; Yuningsih, Dwi; Ratnasari, Nita Yunianti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Continuous Ambulatory Peritoneal Dialysis (CAPD) is a form of chronic peritoneal dialysis for patients with chronic kidney disease. It is carried out 3-5 times per day, 7 days per week with each time the dialysis fluid in the peritoneal cavity (dwelltime) for more than 4 hours. Through so many procedures to go through in each dialysis, it is not uncommon to affect the patient's quality of life.Objectives: To find out the correlation between self-efficacy and the quality of life among patients undergoing continuous ambulatory peritoneal dialysis.Methods: This study is quantitative research with a cross-sectional research design. The population employed all chronic kidney failure patients undergoing CAPD at Kasih Ibu Surakarta Hospital in 2023, with a total of 42 patients. The sample involved 42 samples selected using total sampling technique. Data collection used a self-efficacy questionnaire and quality of life questionnaire which its test consisted of univariate and bivariate using Chi-square testResults: The number of respondents having self-efficacy in the good category as many as 25 respondents (59,5%); the number of respondents with a quality of life in the good category is 29 respondents (69,0%); the Chi Square test results reveal that the amount of p-value obtained is 0,011 (p-value less than 0,05) means there is a correlation between self-efficacy and the quality of life among patients undergoing Continous Ambulatory Peritoneal Dialysis (CAPD) at Kasih Ibu Surakarta Hospital.Conclusions: There is a correlation between self-efficacy and the quality of life among patients undergoing Continous Ambulatory Peritoneal Dialysis (CAPD) at Kasih Ibu Surakarta Hospital with a p-value of 0,018 (<0,05).